DAMPAK IMPOTENSI TERHADAP STABILITAS RUMAH TANGGA DALAM PERSPEKTIF HUKUM ISLAM: STUDI KASUS NO. 18/PDT.G/2022/PA.KP - Husaini, Akhmad; Yassir, Muhammad; Chanif Setiawan, Muchammad (Sekolah Tinggi Dirasat Islamiyah Imam Syafi'i Jember, 2025)
This study examines the psychological, social, and legal impacts of a husband's impotence on marital stability from the perspective of Islamic law, focusing on the Case No. 18/Pdt.G/2022/PA.Kp, decided by the Religious Court of Kupang. The aim of this study is to assess how impotence, as a biological dysfunction, affects the marital relationships and to explore how Islamic law offers legal remedies for couples, particularly for wives. This research employs a qualitative descriptive method by analyzing legal documents, Islamic literature, and relevant court rulings. The findings indicate that impotence has a significant mental and psychological impact impact on both spouses, disrupting emotional intimacy, sexual satisfaction, and overall marital harmony. In Islamic law, impotence is classified as a defect (“aib”) that may serve as a legitimate ground for a wife to seek annulment of the marriage (“fasakh”). The case analysis reveals that the husband's failure to fulfill conjugal rights and the resulting emotional distress constitute valid reasons for divorce. The study concludes that addressing impotence requires a comprehensive approach—medical, psychological, and legal— grounded in compassion and justice as upheld in Islamic teachings. Moreover, education, open communication, and legal protection are essential for safeguarding the rights and dignity of individuals within marital life.